Lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery
By using a combination of precursors and doping elements in the preparation method, the safety risks and conductivity issues of lithium manganese iron phosphate positive electrode materials in lithium-ion batteries are solved, the compaction density and electrochemical properties of the material are improved, and its commercialization process is promoted.
Patent Information
- Application Number
- CN202511332426.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-18
- Publication Date
- 2025-10-24
- Estimated Expiration
- 2045-09-18
AI Technical Summary
Lithium manganese iron phosphate positive electrode materials have safety risks, insufficient compaction density, poor resistance and conductivity, and unstable process in lithium-ion batteries, which hinder their commercialization.
A preparation method of combined precursors and doping elements is adopted. By controlling the metal-phosphorus ratio, particle size and amount of doping elements of the first precursor and the second precursor, lithium manganese iron phosphate materials with different particle sizes are prepared, forming a combination of large and small particles, thereby improving the compaction density and electrical conductivity.
The high-capacity and long-cycle-life lithium manganese iron phosphate material has been achieved, which improves the energy density and safety of lithium-ion batteries and reduces production costs.
Smart Images

Figure CN120829147A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of lithium ion batteries, in particular to a lithium manganese iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery. BACKGROUND
[0002] As one of the key factors affecting the performance of lithium ion batteries, the performance of the positive electrode material directly affects the energy density, safety, cycle stability and cost-effectiveness of the battery.
[0003] Lithium manganese iron phosphate, as a potential positive electrode material, has attracted widespread attention in recent years due to its abundant raw materials, low cost, environmental friendliness and high theoretical specific capacity. Lithium manganese iron phosphate combines the high energy density of lithium manganese phosphate and the stability of lithium iron phosphate, and theoretically can provide higher energy output, making it an ideal choice for improving the performance of lithium ion batteries.
[0004] However, despite the many advantages of lithium manganese iron phosphate, its commercial application still faces a series of challenges: first, safety risks and insufficient tap density. The inherent properties of manganese elements cause structural instability problems in lithium manganese iron phosphate materials during charging and discharging, which not only increases the safety risk of the battery, but also limits the improvement of the tap density of the battery, thereby affecting the energy density of the battery. Second, the problem of resistance conductivity. The resistance conductivity of lithium manganese iron phosphate is relatively low, and the kinetic performance of lithium manganese iron phosphate at large particle size is significantly deteriorated, affecting the charging and discharging rate and efficiency of the battery.
[0005] To improve the above problems, researchers try to improve the performance of lithium manganese iron phosphate through complex surface coating technology and battery structure design. However, these methods have the defect of high cost, and the operation is complex, it is difficult to ensure the stability of the process, further increasing the production cost and quality control difficulty, the improvement effect is not good in practical application, it is difficult to popularize on a large scale.
[0006] In summary, although lithium manganese iron phosphate positive electrode material has great potential to improve the performance of lithium ion batteries in theory, it faces safety risks, insufficient tap density, low cost-effectiveness, poor resistance conductivity and unstable process in practical application, which seriously hinders its commercialization process. Therefore, developing a preparation method that can not only improve the above defects, but also maintain the advantages of lithium manganese iron phosphate material, is of great significance to the further development of lithium ion battery technology. SUMMARY
[0007] The purpose of the present application is to provide a lithium manganese iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery to solve the above problems.
[0008] To achieve the above purpose, the technical scheme adopted by the present application is as follows: A preparation method of a lithium manganese iron phosphate positive electrode material, comprising the following steps: (1) mixing a combined precursor, a lithium source, a saccharide compound, a dispersing agent, a dopant containing a doping element M2, and water, and performing sand milling to obtain a slurry; The doping element M2 includes at least one of Nb, Ti, W, Ni, and Bi, and preferably includes at least one of Nb and Ti; (2) performing spray drying on the slurry to obtain an intermediate powder; (3) performing sintering and crushing on the intermediate powder to obtain the lithium manganese iron phosphate positive electrode material; The combined precursor includes a first precursor and a second precursor. The first precursor includes at least one of manganese iron hydrogen phosphate, amorphous manganese iron phosphate, and ammonium manganese iron phosphate, and preferably includes amorphous manganese iron phosphate. The first precursor further includes a doping element M1, and the doping element M1 includes at least one of Ti, V, Mg, and Zr, and preferably includes at least one of Mg and Zr. The second precursor includes at least one of hydrated manganese iron phosphate, manganese iron pyrophosphate, and crystalline manganese iron phosphate, and preferably includes manganese iron pyrophosphate. The metal-phosphorus ratio of the first precursor is less than or equal to the metal-phosphorus ratio of the second precursor, and the metal-phosphorus ratio refers to the ratio of the molar amount of metal elements (metal elements other than Mn and Fe) to the molar amount of phosphorus elements.
[0009] According to an embodiment of the present application, in step (1), the mass of the first precursor accounts for 20-50% of the mass of the combined precursor, and preferably accounts for 30-40%; and the mass of the second precursor accounts for 50-80% of the mass of the combined precursor, and preferably accounts for 60-70%. And / or, the metal-phosphorus ratio of the first precursor is 0.950-0.970, and the metal-phosphorus ratio of the second precursor is 0.970-0.990. And / or, the D50 particle size of the first precursor is 5-15 μm, and preferably is 8-12 μm; and the D50 particle size of the second precursor is 0.2-6.0 μm, and preferably is 0.5-4.0 μm.
[0010] According to an embodiment of the present application, in step (1), the ratio of the molar amount of the doping element M1 to the total molar amount of manganese and iron in the first precursor is M1 / (Mn+Fe) = 0.002-0.02:1, and preferably is 0.004-0.015:1.
[0011] According to an embodiment of the present application, in step (1), the molar ratio of phosphorus element in the combined precursor to lithium element in the lithium source is 1:(0.98-1.12); And / or, the mass ratio of the combined precursor to the saccharide compound, the dispersant, the dopant is 1:(3-10):(1-9):(0.2-1); And / or, the dispersant comprises at least one of PEG, PVP; And / or, the lithium source comprises at least one of lithium carbonate, lithium dihydrogen phosphate, lithium hydroxide; And / or, the saccharide compound comprises at least one of glucose, sucrose, maltose.
[0012] According to an embodiment of the present application, in step (1), the solid content of the slurry is 25-65%; And / or, the particle size Dv50 of the slurry is 0.15-0.65 μm; And / or, the particle size Dv50 of the intermediate powder is 5-50 μm.
[0013] According to an embodiment of the present application, in step (3), the sintering is carried out under a nitrogen atmosphere; And / or, the sintering temperature is 600-800°C, and the sintering time is 4-15 h; And / or, the pulverization method comprises air flow pulverization, and the particle size Dv50 of the material obtained after pulverization is 0.3-2.5 μm.
[0014] The present application also provides a lithium iron manganese phosphate positive electrode material, which is prepared by the preparation method of the lithium iron manganese phosphate positive electrode material described above; The lithium iron manganese phosphate positive electrode material comprises a first lithium iron manganese phosphate material and a second lithium iron manganese phosphate material, the first lithium iron manganese phosphate material is prepared from a first precursor, the second lithium iron manganese phosphate material is prepared from a second precursor, and the particle size of the first lithium iron manganese phosphate material is larger than that of the second lithium iron manganese phosphate material.
[0015] According to an embodiment of the present application, the primary particle size of the first lithium iron manganese phosphate material is 100-500 nm; The primary particle size of the second lithium iron manganese phosphate material is 20-200 nm.
[0016] According to an embodiment of the present application, the mass of the first lithium iron manganese phosphate material accounts for 20-50% of the total mass of the lithium iron manganese phosphate positive electrode material; And / or, the powder compaction density of the lithium iron manganese phosphate positive electrode material under a 4t pressure is 2.35-2.50 g / cm3 ; and / or, the powder resistivity of the lithium manganese iron phosphate positive electrode material is 5-182 Ω·cm, preferably 5-100 Ω·cm.
[0017] The application also provides a lithium ion battery comprising the lithium manganese iron phosphate positive electrode material prepared by the preparation method of the lithium manganese iron phosphate positive electrode material described above or comprising the lithium manganese iron phosphate positive electrode material described above.
[0018] Compared with the prior art, the application has the following beneficial effects: The first precursor has a lower metal phosphorus ratio, and is easy to form large particles after sintering. The second precursor has a higher metal phosphorus ratio, and is easy to form small particles after sintering. The large particles and the small particles cooperate with each other, which can effectively improve the compaction density of the positive electrode material.
[0019] The application selects at least one of manganese hydrogen phosphate iron, amorphous manganese iron phosphate, and ammonium manganese iron phosphate as the first precursor, which has high sintering reactivity and can form uniform and dense spherical large particle lithium manganese iron phosphate. Such large particle lithium manganese iron phosphate can provide better structural stability and optimize the coating performance of the positive electrode material.
[0020] The application selects at least one of hydrated manganese iron phosphate, manganese iron pyrophosphate, and crystalline manganese iron phosphate as the second precursor, which has a stable structure as a crystalline material and can provide a good crystallization template as a small particle, helping the surrounding area (including the surface of the large particle in contact with it) to form a structured lithium manganese iron phosphate, reducing the generation of impurities, improving the structural uniformity and crystallinity of the product, and such small particle lithium manganese iron phosphate maintains high reactivity, improves the lithium ion diffusion rate, and as a high-activity unit, contributes mainly to the capacity output in the fast-charging scenario.
[0021] The positive electrode material prepared by the method of the application comprises large particles (first lithium manganese iron phosphate material) and small particles (second lithium manganese iron phosphate material), the large particles act as a framework to support the electrode structure, and the small particles fill the gaps, which can effectively fill the gaps between the particles, thereby improving the compaction density of the positive electrode material and forming a dense and stable electrode layer, and reducing the lithium ion transmission resistance.
[0022] The first precursor of the application comprises a doped element M1, which can uniformly dope elements with relatively large ion diameters, effectively overcoming the problem of uneven doping caused by the difference in thermodynamic conditions of large particles in the subsequent sintering process. Through this pre-doping means, the structural stability of the material can be significantly improved, the dissolution of iron and manganese can be inhibited, and the electrical conductivity of the large particles can be improved.
[0023] The dopant of the application contains a doping element M2, which can effectively improve the overall electrochemical performance of the positive electrode material.
[0024] By controlling the amount ratio of the first precursor and the second precursor, the application can make the size particle ratio in the lithium manganese iron phosphate moderate, which is conducive to obtaining the optimal compaction.
[0025] In summary, the above effects can be used to prepare high-capacity, long-cycle, high-compaction lithium manganese iron phosphate materials through a simple process. BRIEF DESCRIPTION OF DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the application, the drawings needed in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the application, and therefore should not be regarded as limiting the scope of the application.
[0027] Figure 1 SEM image of the lithium manganese iron phosphate material prepared for Example 1; Figure 2 SEM image of the lithium manganese iron phosphate material prepared for Comparative Example 2; Figure 3 SEM image of the lithium manganese iron phosphate material prepared for Comparative Example 3. DETAILED DESCRIPTION
[0028] As used herein: “prepared from” is synonymous with “comprising”. The terms “comprising”, “including”, “having” or “with” or any other variation thereof, as used herein, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that comprises a list of elements is not necessarily limited to only those elements but can include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0029] The conjunction “consisting of’ excludes any unrecited elements, steps, or components. If used in the claims, this phrase shall be construed to mean that the claims encompass only those materials described in the specification, unless the contrary intention of the party that filed the application is expressly stated. When the phrase “consisting of’ appears in a clause of the body of the claim, it limits the claim to the elements described in that clause; other elements are not excluded from the claim as a whole.
[0030] When expressing amounts, such as equivalent, concentration, or other values or parameters, as a range, preferably a range, or a series of upper preferred values and lower preferred values, it should be understood that all ranges formed by any pair of an upper or preferred value of a range with a lower or preferred value of a range, whether or not the range is expressly disclosed, are specifically disclosed. For example, when a range "1-5" is disclosed, the described range should be interpreted to include the range "1-4", "1-3", "1-2", "1-2 and 4-5", "1-3 and 5", etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include the endpoints and all integers and fractions within that range.
[0031] In these embodiments, the parts and percentages described are by mass, unless otherwise indicated.
[0032] "Mass parts" refers to a basic unit of measurement that represents the mass ratio relationship of multiple components, 1 part can represent any unit mass, such as 1 g, 2.689 g, etc. If we say that the mass parts of component A is a parts, and the mass parts of component B is b parts, it means that the mass ratio of component A to component B is a:b. Alternatively, it means that the mass of component A is aK, and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that unlike mass parts, the sum of the mass parts of all components is not limited to 100 parts.
[0033] "And / or" is used to indicate that one or both of the described conditions can occur, for example, A and / or B includes (A and B) and (A or B).
[0034] In order to better illustrate the technical solutions provided in the present application, before the embodiments, the technical solutions are stated as a whole, as follows: A preparation method of a lithium iron manganese phosphate positive electrode material, comprising the following steps: (1) mixing a combined precursor, a lithium source, a saccharide compound, a dispersing agent, a dopant containing a doping element M2, and water, and performing sand milling to obtain a slurry; The doping element M2 includes at least one of Nb, Ti, W, Ni, and Bi, and preferably includes at least one of Nb and Ti; (2) performing spray drying on the slurry to obtain an intermediate powder; (3) performing sintering and crushing on the intermediate powder to obtain the lithium iron manganese phosphate positive electrode material; The combined precursor includes a first precursor and a second precursor. The first precursor includes at least one of manganese iron hydrogen phosphate, amorphous manganese iron phosphate, and ammonium manganese iron phosphate, and preferably includes amorphous manganese iron phosphate. The first precursor further comprises a doping element M1, the doping element M1 comprises at least one of Ti, V, Mg, Zr, and preferably at least one of Mg and Zr; The second precursor comprises at least one of hydrated manganese iron phosphate, manganese iron pyrophosphate, and crystalline manganese iron phosphate, and preferably comprises manganese iron pyrophosphate. The metal phosphorus ratio of the first precursor is less than or equal to the metal phosphorus ratio of the second precursor, and the metal phosphorus ratio refers to the ratio of the molar amount of metal elements to the molar amount of phosphorus elements.
[0035] In the case of a high metal phosphorus ratio, the surface proportion of phosphorus-oxygen tetrahedron for constructing a particle skeleton is low, and the particles are not easy to grow and fuse, and on the contrary, the components with a low metal phosphorus ratio are easy to generate large particles. The first precursor of the present application has a property of being easy to grow, and the second precursor has a property of being not easy to grow. The first precursor with a lower metal phosphorus ratio and the second precursor with a higher metal phosphorus ratio in the present application are mutually matched, which is beneficial to the uniform distribution of the interstitial space in space. Specifically, the first precursor also has a lower metal phosphorus ratio, and the precursor with a lower metal phosphorus ratio is easy to form large particles after sintering. The second precursor has a higher metal phosphorus ratio, and the precursor with a higher metal phosphorus ratio is easy to form small particles after sintering. After sintering, the positive electrode material can include particles with a large particle size and particles with a small particle size, and the particles with a large particle size and the particles with a small particle size are mutually matched, which can effectively improve the compaction density of the positive electrode material. Moreover, the first precursor has pores in the interior, which is beneficial to the more sufficient contact with the electrolyte and is more beneficial to the migration of lithium ions.
[0036] According to the embodiments of the present application, the first precursor further comprises a doping element M1, the doping element M1 comprises at least one of Ti, V, Mg, Zr, and these elements can control the phosphate crystal structure, expand the lithium ion transmission channel, and adjust the energy band structure. By introducing the doping element M1 into the first precursor, the problems of insufficient ion conductivity and electronic conductivity of large particles can be compensated.
[0037] Further, the first precursor can be prepared by a co-precipitation method, and the M1 element can be introduced in the preparation process, so that the first precursor contains the doping element M1.
[0038] The introduction of the doping element M2 can form a fast ion conductor on the surface of the material, improve the lithium ion transfer capacity on the interface of the material, improve the kinetic performance, and small particles can optimize the kinetics by doping M2, and large particles can further optimize the kinetics.
[0039] According to some embodiments of the present application, the dopant can be an oxide of the doping element M2, for example, the dopant can be niobium oxide and / or titanium oxide.
[0040] According to the embodiments of the present application, in step (1), the mass of the first precursor accounts for 20-50%, preferably 30-40%, of the mass of the combined precursor, and the mass of the second precursor accounts for 50-80%, preferably 60-70%, of the mass of the combined precursor. If the content of the first precursor is too low, the electrical performance defects of the lithium manganese iron material will be amplified, and capacity and kinetic defects will be easily caused.
[0041] For example, the mass of the first precursor can account for 20%, 25%, 30%, 35%, 40%, 45%, 50% or any value between 20-50% of the mass of the combined precursor, and the mass of the second precursor can account for 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value between 50-80% of the mass of the combined precursor.
[0042] For example, the mass of the first precursor can account for 20%, 25%, 30%, 35%, 40%, 45%, 50% or any value between 20-50% of the mass of the combined precursor, and the mass of the second precursor can account for 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value between 50-80% of the mass of the combined precursor. For example, the mass of the first precursor can account for 20%, 25%, 30%, 35%, 40%, 45%, 50% or any value between 20-50% of the mass of the combined precursor, and the mass of the second precursor can account for 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value between 50-80% of the mass of the combined precursor.
[0043] For example, the mass of the first precursor can account for 20%, 25%, 30%, 35%, 40%, 45%, 50% or any value between 20-50% of the mass of the combined precursor, and the mass of the second precursor can account for 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value between 50-80% of the mass of the combined precursor.
[0044] According to the embodiments of the present application, in step (1), the ratio of the molar amount of the doping element M1 to the total molar amount of manganese and iron in the first precursor, M1 / (Mn+Fe), is 0.002-0.02:1, preferably 0.004-0.015:1. When the content of the doping element M1 is within the above range, the kinetic performance of the positive electrode material is improved. If the content of the doping element M1 is too high, the first precursor cannot achieve the required metal phosphorus ratio, and the morphology will also be damaged.
[0045] For example, the ratio of the molar amount of the doping element M1 to the total molar amount of manganese and iron in the first precursor M1 / (Mn+Fe) can be 0.002:1, 0.004:1, 0.006:1, 0.008:1, 0.01:1, 0.012:1, 0.014:1, 0.015:1, 0.016:1, 0.018:1, 0.02:1, or any value between 0.002 and 0.02:1.
[0046] According to an embodiment of the present application, in step (1), the molar ratio of the phosphorus element in the combined precursor to the lithium element in the lithium source is 1:(0.98-1.12); For example, the molar ratio of the phosphorus element in the combined precursor to the lithium element in the lithium source can be 1:0.98, 1:1, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.10, 1:1.12, or any value between 1:(0.98-1.12).
[0047] And / or, the mass ratio of the combined precursor to the saccharide compound, the dispersant, and the dopant is 1:(3-10)%:(1-9)%:(0.2-1)%. When the mass ratio of the combined precursor to the saccharide compound, the dispersant, and the dopant is within the above range, the positive electrode material can simultaneously have good electrical conductivity, processing performance, kinetic performance, and high stability.
[0048] For example, the mass ratio of the combined precursor to the saccharide compound, the dispersant, and the dopant can be 1:3%:1%:0.2%, 1:5%, 5%, 0.5%, 1:10%:9%:1%, or any value between 1:(3-10)%:(1-9)%:(0.2-1)%.
[0049] The saccharide compound has a reducing and carbon-coating effect. Further, if the content of the saccharide compound is too low, the electrical conductivity of the positive electrode material will be insufficient, and if the content of the saccharide compound is too high, the processing performance will be affected.
[0050] If the content of the dispersant is too low, the morphology and electrical conductivity of the positive electrode material will be poor. If the content of the dispersant is too high, the viscosity will be too large, which is not conducive to the process.
[0051] The main function of the dopant is doping, and it also has a coating effect. If the content of the dopant is too low, the kinetic performance of the positive electrode material will be insufficient. If the content of the dopant is too high, the particle growth will be abnormal, reducing the tap density. And / or, the dispersant comprises at least one of PEG, PVP; the addition of the dispersant helps to improve the dispersion effect between different raw materials, improve the uniformity and consistency of the material, optimize the morphology and size distribution of the positive electrode material particles, and thus improve the overall performance and stability of the positive electrode material.
[0052] And / or, the lithium source comprises at least one of lithium carbonate, lithium dihydrogen phosphate, lithium hydroxide; And / or, the saccharide compound comprises at least one of glucose, sucrose, maltose.
[0053] According to an embodiment of the present application, in step (1), the solid content of the slurry is 25-65%; And / or, the particle size Dv50 of the slurry is 0.15-0.65 μm; if the particle size Dv50 of the slurry is too low, the energy consumption of sanding is high, and the growth rate is too fast in the sintering process, resulting in uneven microstructure of the positive electrode material and affecting the electrochemical performance of the positive electrode material. If the particle size Dv50 of the slurry is too high, the uniformity of the material is poor, resulting in poor electrochemical performance of the positive electrode material.
[0054] Further, the sanding comprises coarse sanding and fine sanding. Through coarse sanding, large particles in the slurry can be rapidly broken and the particle size thereof can be reduced. Fine sanding is a more fine grinding after coarse sanding. Fine sanding can grind the slurry more finely, making the particle size more uniform and the fineness higher.
[0055] And / or, the particle size Dv50 of the intermediate powder is 5-50 μm.
[0056] In some embodiments, in step (2), the temperature of spray drying is 250°C, 260°C, 270°C, or any value between 250-270°C.
[0057] According to an embodiment of the present application, in step (3), the sintering is carried out under a nitrogen atmosphere; And / or, the temperature of sintering is 600-800°C, and the time of sintering is 4-15 h; For example, the temperature of sintering can be 600°C, 650°C, 700°C, 750°C, 800°C, or any value between 600-800°C, and the time of sintering can be 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, or any value between 4-15 h.
[0058] If the temperature of sintering is too low, the particle growth will be insufficient, affecting the electrochemical performance and mechanical performance of the material. If the temperature of sintering is too high, the particle will grow excessively, resulting in poor charge-discharge performance.
[0059] and / or, the pulverizing method comprises air flow pulverization, and the particle size Dv50 of the material obtained after the pulverization is 0.3-2.5 μm, preferably 0.3-0.8 μm.
[0060] The application also provides a lithium iron manganese phosphate positive electrode material, which is prepared by the method for preparing a lithium iron manganese phosphate positive electrode material described above. The lithium iron manganese phosphate positive electrode material comprises a first lithium iron manganese phosphate material and a second lithium iron manganese phosphate material, the first lithium iron manganese phosphate material is prepared from a first precursor, the second lithium iron manganese phosphate material is prepared from a second precursor, and the particle size of the first lithium iron manganese phosphate material is larger than that of the second lithium iron manganese phosphate material.
[0061] According to the embodiments of the application, the primary particle size of the first lithium iron manganese phosphate material is 100-500 nm. The primary particle size of the second lithium iron manganese phosphate material is 20-200 nm.
[0062] According to the embodiments of the application, the mass of the first lithium iron manganese phosphate material accounts for 20%-50% of the total mass of the lithium iron manganese phosphate positive electrode material. and / or, the powder compaction density of the lithium iron manganese phosphate positive electrode material under a pressure of 4 t is 2.35-2.50 g / cm 3 ; and / or, the powder resistivity of the lithium iron manganese phosphate positive electrode material is 5-182 Ω·cm.
[0063] According to some embodiments of the application, the 1C discharge gram capacity of the lithium iron manganese phosphate positive electrode material is 144 mAh / g or more, and the 0.1C discharge gram capacity of the lithium iron manganese phosphate positive electrode material is 155 mAh / g or more.
[0064] The application also provides a lithium ion battery comprising the lithium iron manganese phosphate positive electrode material prepared by the method for preparing a lithium iron manganese phosphate positive electrode material described above or comprising the lithium iron manganese phosphate positive electrode material described above.
[0065] The embodiments of the application will be described in detail below with reference to specific examples, but those skilled in the art will understand that the following examples are only used to illustrate the application and should not be regarded as limiting the scope of the application. If no specific conditions are indicated in the examples, the conventional conditions or the conditions recommended by the manufacturer are used. If no manufacturer of the reagents or instruments is indicated, it is a conventional product that can be purchased on the market.
[0066] Example 1 S1: weigh the combined precursor, lithium source, sugar compound, dispersant and dopant.
[0067] The combined precursor is composed of a first precursor and a second precursor. The first precursor is an amorphous manganese iron phosphate with a metal-phosphorus ratio (Mn+Fe) / P of 0.9625, and the first precursor further comprises a doping element Mg. The molar ratio of the doping element Mg to the metal elements of the first precursor is 0.01:1. The D50 particle size of the first precursor is 10 μm. The second precursor is a manganese iron pyrophosphate with a metal-phosphorus ratio (Mn+Fe) / P of 0.975, and the D50 particle size of the second precursor is 3 μm. The mass of the first precursor accounts for 35% of the mass of the combined precursor, and the mass of the second precursor accounts for 65% of the mass of the combined precursor.
[0068] The lithium source is lithium carbonate, and the molar ratio of the phosphorus element in the combined precursor to the lithium element in the lithium source is 1:1.08.
[0069] The saccharide compound is sucrose, the dispersant is polyethylene glycol (PEG), and the dopant comprises niobium oxide and titanium oxide, wherein the mass ratio of the niobium oxide to the titanium oxide is 2:1.
[0070] The mass ratio of the combined precursor to the saccharide compound, the dispersant, and the dopant is 1:5%:5%:0.5%.
[0071] The weighed combined precursor, lithium source, saccharide compound, dispersant, and dopant are dispersed in pure water to obtain a slurry mixture, and the solid content of the slurry mixture is 30%.
[0072] S2: The slurry is coarsely ground until the particle size Dv50 is 1.0-2.0 μm. Then, the slurry is transferred to fine grinding, and sand grinding is performed until the particle size Dv50 is 0.35-0.40 μm. S3: The slurry treated in S2 is spray dried at 260°C to obtain a spray powder, and an intermediate powder is obtained, wherein the Dv50 of the intermediate powder is 20-50 μm. S4: The intermediate powder obtained in S3 is sintered in a nitrogen atmosphere, and the sintering temperature is controlled at 720±5°C, and the sintering time is 8 h, to obtain a lithium manganese iron phosphate agglomerate. The lithium manganese iron phosphate agglomerate is subjected to jet milling to obtain a lithium manganese iron phosphate positive electrode material, and the particle size Dv50 of the lithium manganese iron phosphate positive electrode material is controlled to be 0.4±0.1 μm.
[0073] The SEM image of the lithium manganese iron phosphate material prepared in Example 1 is as shown in Figure 1The lithium manganese iron phosphate positive electrode material includes a first lithium manganese iron phosphate material and a second lithium manganese iron phosphate material, the first lithium manganese iron phosphate material is prepared from a first precursor, the second lithium manganese iron phosphate material is prepared from a second precursor, and the particle size of the first lithium manganese iron phosphate material is larger than that of the second lithium manganese iron phosphate material. The primary particle size of the first lithium manganese iron phosphate material is 100-500 nm, and the primary particle size of the second lithium manganese iron phosphate material is 20-200 nm.
[0074] The mass of the first lithium manganese iron phosphate material accounts for 20%-50% of the total mass of the lithium manganese iron phosphate positive electrode material.
[0075] Example 2 The lithium manganese iron phosphate positive electrode material is prepared by the method of Reference Example 1, and other parameters are the same as those in Example 1, except that the mass of the first precursor accounts for 30% of the mass of the combined precursor, and the mass of the second precursor accounts for 70% of the mass of the combined precursor.
[0076] Example 3 The lithium manganese iron phosphate positive electrode material is prepared by the method of Reference Example 1, and other parameters are the same as those in Example 1, except that the mass of the first precursor accounts for 40% of the mass of the combined precursor, and the mass of the second precursor accounts for 60% of the mass of the combined precursor.
[0077] Example 4 The lithium manganese iron phosphate positive electrode material is prepared by the method of Reference Example 1, and other parameters are the same as those in Example 1, except that the mass ratio of the combined precursor, the saccharide compound, the dispersing agent, and the dopant is 1:5%:5%:0.2%.
[0078] Example 5 The lithium manganese iron phosphate positive electrode material is prepared by the method of Reference Example 1, and other parameters are the same as those in Example 1, except that the mass ratio of the combined precursor, the saccharide compound, the dispersing agent, and the dopant is 1:5%:5%:1%.
[0079] Example 6 The lithium manganese iron phosphate positive electrode material is prepared by the method of Reference Example 1, and other parameters are the same as those in Example 1, except that the dopant only includes niobium oxide.
[0080] Example 7 The lithium manganese iron phosphate positive electrode material is prepared by the method of Reference Example 1, and other parameters are the same as those in Example 1, except that the dopant only includes titanium oxide.
[0081] Example 8 The lithium manganese iron phosphate positive electrode material was prepared by the method of Reference Example 1, and other parameters were the same as those of Example 1, except that the first precursor was ammonium manganese iron phosphate with a metal-phosphorus ratio (Mn+Fe) / P of 0.9625, and the second precursor was crystalline manganese iron phosphate with a metal-phosphorus ratio (Mn+Fe) / P of 0.975.
[0082] Comparative Example 1 The lithium manganese iron phosphate positive electrode material was prepared by the method of Reference Example 1, and other parameters were the same as those of Example 1, except that the second precursor was manganese iron pyrophosphate with a metal-phosphorus ratio (Mn+Fe) / P of 0.945.
[0083] Comparative Example 2 The lithium manganese iron phosphate positive electrode material was prepared by the method of Reference Example 1, and other parameters were the same as those of Example 1, except that no first precursor was added.
[0084] The SEM image of the lithium manganese iron phosphate material prepared in Comparative Example 2 is shown in FIG. 2. Figure 2
[0085] Comparative Example 3 The lithium manganese iron phosphate positive electrode material was prepared by the method of Reference Example 1, and other parameters were the same as those of Example 1, except that no second precursor was added.
[0086] The SEM image of the lithium manganese iron phosphate material prepared in Comparative Example 3 is shown in FIG. 3. Figure 3
[0087] Comparative Example 4 The lithium manganese iron phosphate positive electrode material was prepared by the method of Reference Example 1, and other parameters were the same as those of Example 1, except that the doping element Mg was not included in the first precursor.
[0088] Comparative Example 5 The lithium manganese iron phosphate positive electrode material was prepared by the method of Reference Example 1, and other parameters were the same as those of Example 1, except that no dopant was added.
[0089] Test process of button cell The positive electrode materials prepared in the examples and comparative examples were mixed with PVDF and NMP in a ratio of 90:5:5 to prepare a positive electrode slurry, which was coated on an aluminum foil, dried, punched, and cut to obtain a positive electrode sheet. In a glove box, a button cell was assembled by assembling the positive electrode sheet with a lithium sheet, a separator, and an electrolyte. The assembled button cell was placed in a mold groove of a hydraulic sealing machine, locked, pressed, then unlocked, and the sealed button cell was taken out. The separator was a Celgard polypropylene film, and the electrolyte was purchased from Xinyashengshanjian New Material Technology Co., Ltd. The test is carried out by using a blue and (model: CT3002A) battery test cabinet, the test voltage range is 2.0 V-4.5 V, specifically, 0.1C constant current charging to 4.5 V, constant voltage charging to 50 μA, 0.1C discharging to 2.0 V, the above is regarded as the first cycle, and the discharge capacity after the first cycle is recorded as the 0.1C discharge gram capacity (mAh / g); again, 1C constant current charging to 4.5 V, constant voltage charging to 50 μA, 1C discharging to 2.0 V, the discharge capacity after the second cycle is recorded as the 1C discharge gram capacity (mAh / g); again, continue to charge to 4.5 V at 1C constant current, constant voltage charging to 50 μA, 1C discharging to 2.0 V, repeat the above operation, and the discharge capacity after the fifty-first cycle is recorded as the 1C discharge gram capacity after 50 cycles (mAh / g).
[0090] The performance data of examples 1-8 and comparative examples 1-5 are shown in table 1.
[0091] Table 1 performance comparison table of examples 1-8 and comparative examples 1-5
[0092] In table 1, the "powder compaction density" refers to the powder compaction density of the lithium manganese iron phosphate positive electrode material under 4t pressure.
[0093] As can be seen from table 1, the powder compaction density of the lithium manganese iron phosphate positive electrode material of examples 1-8 is 2.36-2.46 g / cm 3 , the resistivity is 30-82 Ω·cm, and the particle size Dv50 is 0.37-0.47 μm.
[0094] Compared with comparative examples 1-5, examples 1-8 have higher 0.1C discharge gram capacity, 1C discharge gram capacity, initial efficiency and 1C discharge gram capacity after 50 cycles, which indicates that the examples have more excellent comprehensive electrochemical performance.
[0095] Specifically, the comprehensive electrochemical performance of comparative example 1 is poor, which may be caused by the fact that the metal phosphorus ratio of the first precursor in comparative example 1 is greater than that of the second precursor.
[0096] The comprehensive electrochemical performance of comparative example 2 is poor, which may be caused by not adding the combined precursor.
[0097] The comprehensive electrochemical performance of comparative example 3 is poor, which may be caused by not adding the combined precursor in the preparation method.
[0098] The comprehensive electrochemical performance of comparative example 4 is poor, which may be caused by not including the doping element in the first precursor.
[0099] The comprehensive electrochemical performance of Comparative Example 5 is poor, which can be caused by the absence of dopant in the preparation method.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, and are not intended to limit the same; although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the foregoing embodiments, or make equivalent replacements for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
[0101] In addition, those skilled in the art can understand that although some embodiments herein include certain features rather than others included in other embodiments, the combination of features of different embodiments means to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments can be used in any combination. The information disclosed in the BACKGROUND section is only intended to deepen the understanding of the overall background of the present application, and should not be regarded as acknowledging or implying in any form that the information constitutes the prior art known to those skilled in the art.
Claims
1. A method for preparing a lithium iron manganese phosphate cathode material, characterized in that, The method comprises the following steps: (1) mixing a combined precursor, a lithium source, a sugar compound, a dispersant, a dopant containing a doping element M2, and water, and performing sanding to obtain a slurry; The doping element M2 includes at least one of Nb, Ti, W, Ni, and Bi; (2) performing spray drying on the slurry to obtain an intermediate powder; (3) performing sintering and crushing on the intermediate powder to obtain the lithium manganese iron phosphate positive electrode material; The combined precursor includes a first precursor and a second precursor; The first precursor includes at least one of manganese iron hydrogen phosphate, amorphous manganese iron phosphate, and ammonium manganese iron phosphate; The first precursor further includes a doping element M1, and the doping element M1 includes at least one of Ti, V, Mg, and Zr; The second precursor includes at least one of hydrated manganese iron phosphate, manganese iron pyrophosphate, and crystalline manganese iron phosphate; The metal-phosphorus ratio of the first precursor is less than or equal to the metal-phosphorus ratio of the second precursor, and the metal-phosphorus ratio refers to the ratio of the molar amount of metal elements to the molar amount of phosphorus elements.
2. The method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1, wherein: In step (1), the mass of the first precursor accounts for 20-50% of the mass of the combined precursor, and the mass of the second precursor accounts for 50-80% of the mass of the combined precursor; And / or, the metal-phosphorus ratio of the first precursor is 0.950-0.970, and the metal-phosphorus ratio of the second precursor is 0.970-0.990; And / or, the D50 particle size of the first precursor is 5-15 μm, and the D50 particle size of the second precursor is 0.2-6.0 μm.
3. The method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step (1), the ratio of the molar amount of the doping element M1 to the total molar amount of manganese and iron in the first precursor is M1 / (Mn+Fe)=0.002-0.02:
1.
4. The method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step (1), the molar ratio of phosphorus elements in the combined precursor to lithium elements in the lithium source is 1:(0.98-1.12); And / or, the mass ratio of the combined precursor to the sugar compound, the dispersant, and the dopant is 1:(3-10)%:(1-9)%:(0.2-1)%; And / or, the dispersant includes at least one of PEG and PVP; And / or, the lithium source includes at least one of lithium carbonate, lithium dihydrogen phosphate, and lithium hydroxide; And / or, the sugar compound includes at least one of glucose, sucrose, and maltose.
5. The method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step (1), the solid content of the slurry is 25-65%; And / or, the particle size Dv50 of the slurry is 0.15-0.65 μm; And / or, the particle size Dv50 of the intermediate powder is 5-50 μm.
6. The method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step (3), the sintering is performed in a nitrogen atmosphere; And / or, the sintering temperature is 600-800 ℃, and the sintering time is 4-15 h; And / or, the crushing mode includes air flow crushing, and the particle size Dv50 of the material obtained after crushing is 0.3-2.5 μm.
7. A lithium iron manganese phosphate cathode material, characterized in that, The lithium manganese iron phosphate positive electrode material is prepared by the preparation method of the lithium manganese iron phosphate positive electrode material according to any one of claims 1-6. The lithium manganese iron phosphate positive electrode material comprises a first lithium manganese iron phosphate material and a second lithium manganese iron phosphate material, the first lithium manganese iron phosphate material is prepared from a first precursor, the second lithium manganese iron phosphate material is prepared from a second precursor, and the particle size of the first lithium manganese iron phosphate material is larger than that of the second lithium manganese iron phosphate material.
8. The lithium iron manganese phosphate cathode material of claim 7, wherein, The primary particle size of the first lithium manganese iron phosphate material is 100-500 nm. The primary particle size of the second lithium manganese iron phosphate material is 20-200 nm.
9. The lithium iron manganese phosphate cathode material according to claim 7 or 8, characterized in that The mass of the first lithium manganese iron phosphate material accounts for 20%-50% of the total mass of the lithium manganese iron phosphate positive electrode material. And / or, the powder compaction density of the lithium manganese iron phosphate positive electrode material under 4t pressure is 2.35~2.50g / cm 3 ; And / or, the powder resistivity of the lithium manganese iron phosphate positive electrode material is 5-182 Ω·cm.
10. A lithium-ion battery, characterized by, The lithium manganese iron phosphate positive electrode material prepared by the preparation method of the lithium manganese iron phosphate positive electrode material according to any one of claims 1-6 or the lithium manganese iron phosphate positive electrode material according to any one of claims 7-9.
Citation Information
Patent Citations
Preparation method of lithium manganese iron phosphate material, lithium manganese iron phosphate material and lithium ion battery
CN117486184A
Ferric manganese phosphate precursor, lithium ferric manganese phosphate and preparation method thereof
CN118004990A
Lithium manganese iron phosphate positive electrode material and preparation method thereof, lithium ion battery and electric equipment
CN120319802A
Lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery
CN120389032A
Preparation method for ammonium manganese iron phosphate, and lithium manganese iron phosphate and use thereof
US20250214841A1